1998
DOI: 10.1029/98jb02795
|View full text |Cite
|
Sign up to set email alerts
|

The size distribution of pyroclasts and the fragmentation sequence in explosive volcanic eruptions

Abstract: Abstract. In an explosive eruption, the atmospheric column dynamics depend strongly on the mass fraction of gas in the erupting mixture, which is fixed by fragmentation in the volcanic conduit. At fragmentation, gas present in vesicular magmatic liquid gets partitioned between a continuous phase separating magma clasts and a dispersed phase in individual bubbles within the clasts. As regards flow behavior, it is the former, continuous, gas phase which matters, and we show that its amount is determined by the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
175
2
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(208 citation statements)
references
References 73 publications
14
175
2
16
Order By: Relevance
“…Our simulations confirmed that the power law bubble distributions did not alter this value (Fig. 4a) which is very close to the empirical value B 3,f ≈1.1±0.1 from Plinian fragments (Kaminski and Jaupart, 1998). Note that in some of the literature (e.g.…”
Section: -D Continuum Percolation: Power Law and Monodisperse Bubblesupporting
confidence: 76%
See 3 more Smart Citations
“…Our simulations confirmed that the power law bubble distributions did not alter this value (Fig. 4a) which is very close to the empirical value B 3,f ≈1.1±0.1 from Plinian fragments (Kaminski and Jaupart, 1998). Note that in some of the literature (e.g.…”
Section: -D Continuum Percolation: Power Law and Monodisperse Bubblesupporting
confidence: 76%
“…Figure 4b shows that -at least in the case of power law bubble distributions -that the primary fragments have size distributions with long tails not too far from the theoretical power law with exponent B 3f (hence close to the observations of Kaminski and Jaupart, 1998). The only direct way to test this model would be either empirically by testing the yield strengths of volcanic products as functions of their vesicularities (something which to our knowledge has not yet been done systematically), or to perform (difficult) numerical or theoretical calculations on percolating systems (see however below).…”
Section: -D Continuum Percolation As a Model For Explosive Volcanismmentioning
confidence: 88%
See 2 more Smart Citations
“…En este contexto se entenderá por fragmentación secundaria aquella en la cual la partícula, como consecuencia de colisiones se fragmenta, dejando expuesta una porción de las vesículas que contiene en su interior, favoreciendo una subsecuente fracturación al explotar las vesículas debido a que su presión interna es mucho mayor que la externa (Kaminski & Jaupart, 1997, 1998.…”
Section: Introductionunclassified